This will not pass : Trump, Biden and the battle for America's future - Martin, Jonathan (Newspaper reporter); Burns, Alexander (Journalist) (Simon & Schuster, 2022)
With stunning, in-the-room detail, New York Times reporters Jonathan Martin and Alexander Burns show how both our political parties confronted a series of national traumas, including the coronavirus pandemic, the January 6 attack on the Capitol, and the political brinksmanship of President Biden's first year in the White House. From Donald Trump's assault on the 2020 election and his ongoing campaign of vengeance against his fellow Republicans, to the behind-the-scenes story of Biden's selection of Kamala Harris as his running mate and his bitter struggles to unite the Democratic Party, this book exposes the degree to which the two-party system has been strained to the point of disintegration. More than at any time in recent history, the long-established traditions and institutions of American politics are under siege as a set of aging political leaders struggle to hold together a changing country.